2006
DOI: 10.1542/peds.2004-2292
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Candidiasis Among Extremely Low Birth Weight Infants: Risk Factors, Mortality Rates, and Neurodevelopmental Outcomes at 18 to 22 Months

Abstract: Blood cultures were negative for approximately one half of the infants with Candida meningitis. Persistent candidiasis was common. Delayed catheter removal was associated with increased death and NDI rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
539
8
23

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 604 publications
(592 citation statements)
references
References 16 publications
22
539
8
23
Order By: Relevance
“…10 In a recent multi-center study, 5% (14/293) of candidemic infants had Candida meningitis. 1 In our study of infants receiving an LP, 9% (7/77) of candidemic infants had evidence of Candida meningitis. Further, the majority (63%, 12/19) of infants with Candida meningitis had negative blood cultures for Candida.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…10 In a recent multi-center study, 5% (14/293) of candidemic infants had Candida meningitis. 1 In our study of infants receiving an LP, 9% (7/77) of candidemic infants had evidence of Candida meningitis. Further, the majority (63%, 12/19) of infants with Candida meningitis had negative blood cultures for Candida.…”
Section: Discussionmentioning
confidence: 59%
“…1,12 We observed 13% mortality (8/61) of candidemic infants and only 6% (3/51) in those infants with candidemia and culture-negative CSF for Candida. However, 41% (7/17) of infants with culture-positive Candida meningitis and 71% (5/7) of the infants with both positive blood and CSF cultures for Candida died.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, this organism has increased in prevalence in recent years. C. parapsilosis is a common cause of bloodstream infection in neonates [3-5], and has overtaken C. albicans in frequency of hospital-acquired infection in some hospitals worldwide [4, 6, 7]. Recent studies have identified the importance of secreted lipase in the virulence of this organism and have documented its ability to damage tissue in vitro [8, 9].…”
Section: Introductionmentioning
confidence: 99%